The Presence of angiographic collaterals in Non-ST elevation myocardial infarction is a predictor of long-term clinical outcomes - Kloepfer, Angela M.; Lipson, Lewis C.; Keeley, Ellen C. (Catheterization and cardiovascular interventions, 2014)
Objectives To determine whether the presence of angiographic coronary collaterals is a predictor of long‐term clinical outcomes in patients with non‐ST elevation myocardial infarction (NSTEMI). Background The presence of coronary collaterals on angiography provides prognostic information in patients with STEMI, but it is unknown whether they provide prognostic information in patients with NSTEMI. Methods This was a prospective cohort study of 931 consecutive patients undergoing coronary angiography of which 269 (29%) had a NSTEMI. Baseline characteristics, angiographic details, and long‐term clinical outcomes including death, recurrent MI, coronary artery bypass graft surgery (CABG), percutaneous coronary intervention (PCI), stroke, and congestive heart failure (CHF) were collected. Each clinical outcome as well as the combined endpoint of death, recurrent MI, CABG, PCI stroke and CHF was compared in subjects with and without collaterals. Results At one year, individuals with collaterals had significantly increased rates of the combined endpoint compared with those without (25% vs. 16%, P = 0.0001). On multivariate analysis, the presence of collaterals was a strong predictor of the combined endpoint of death, recurrent MI, CABG, PCI, stroke and CHF (HR 1.95, CI 95% 1.08−3.52; P = 0.027). Similarly, in the subset of 115 patients (43%) in whom the culprit artery was identified, the presence of collaterals was a strong negative predictor (HR 3.71, CI 1.31−10.57, P = 0.014), driven by a 13‐fold increase in subsequent CABG. Conclusions In patients with NSTEMI the presence of angiographic coronary collaterals is a predictor of long‐term clinical outcomes primarily driven by increased rates of surgical revascularization. © 2013 Wiley Periodicals, Inc.